Application of solution blow spinning to rapidly fabricate natamycin-loaded gelatin/zein/polyurethane antimicrobial nanofibers for food packaging. (September 2021) - Shen, Chaoyi; Cao, Yang; Rao, Jingshan; Zou, Yucheng; Zhang, Hui; Wu, Di; Chen, Kunsong
Graphical abstract: Highlights: Solution blow spinning (SBS) was used to develop gelatin/zein/polyurethane nanofibers. The SBS process reached a rapid feed rate of 3 mL/h, showing a good fiber production efficiency. The addition of polyurethane improved the flexibility and ductility of the nanofibers. The gelatin/zein/polyurethane nanofibers continuously released natamycin for 240 h. The fibers showed the antimicrobial activity against B. cinerea and A. alternate . Abstract: In this study, solution blow spinning (SBS) was used to rapidly develop gelatin/zein/polyurethane (PU) complex nanofibers for application in food antimicrobial packaging. The mean diameters of the gelatin/zein side were between 569.1 nm and 681.7 nm. The thermal stability of the nanofibers was improved caused by the formed hydrogen bonds between natamycin and the proteins. The water contact angle was increased with natamycin mixed in, suggesting that the hydrophobicity of the fibers improved. The addition of PU improved the elongation at break of the nanofibers from 13.58 % to 531.38 %. Moreover, the nanofibers showed a continuous release of natamycin for 240 h, and possessed good antimicrobial activity against Botrytis cinerea and Alternaria alternate . In addition, the use of SBS technology to fabricate nanofibers obtained a rapid feed rate of 3 mL/h, indicating that SBS is a promising technology to rapidly develop nanofibers for food packaging.